Beetlejuice. Season four, part two [videorecording (DVD)] - Elfman, Danny (Shout! Factory, 2013)
Beetlejuice is the name of a wild bug-eating ghost from the Netherworld with a bad habit of acting stupid and a weakness for not working well with others. His best friend Lydia is a mortal who, despite being best friends, is consistently getting pranks pulled on her by Beetlejuice. Trapped in the Netherworld, the only way Beetlejuice can visit the Outerworld (mortal world) is when his name is repeated three times, but unfortunately for him that is the same way to send him back.